Effect of United Nations Development Programmes on Quality of Primary Education in Abuja - Kelechi , Onwukwe Maureen; Peter, Ossai Onyeka (Kashere Journal of Politics and International Relations, 2024)
The study is to examine the effect of United Nations Development Programmes (UNDP) on Education in the Federal Capital Territory, Abuja (measured by financial resources, policy implementation and government commitment). Education plays a pivotal role in shaping societies and fostering sustainable development. Grounded in the context of improving access to quality, and equity in education, this research investigates the extent to which UNDP initiatives have contributed to educational advancements in the FCT. The study employs a survey research design to analyse the relationship between UNDP and access to quality education as well as the challenges and successes of the programme. A total of 278 respondents were selected randomly for the study. The data for the study was collected through a close-ended questionnaire and subjected to analysis using descriptive statistics of frequency and simple percentage technique. Findings revealed that UNDP programmes have not significantly impacted on the quality of education in the FCT, Abuja. Again, the challenge faced majorly is that of infrastructural deficits and evidence from the research revealed that the greatest success achieved with the UNDP initiative in education is the synergy among stakeholders. In conclusion, this study contributes to understanding how UNDP initiatives shape education in the FCT, highlighting successes and challenges. The study recommends improve funding to ensure the sustainability of intervention and the actives participation of community. The findings offer insights for policymakers, educators, and development practitioners aiming to enhance education within the region.